Infiltration Well Efficacy in Ciliwung Basin Based on Rainfall-Runoff Volumetric Analysis - Jiwa Ksatria, Natio; Hidayatullah, Taofik; Hasan, Fuad; Ersyi Darfia, Novreta; Syarvina; Kumaryadi, Muhammad Rizky (JURNAL SAINTIS, 2022)
[EN] Run-off management is the main challenge of every big city. Land availability, project timeframe, and financing are several issues regarding run-off management implementation, including Indonesia’s Capital City, Jakarta. One of the engineering tools that used to reduce the negative impacts of run-off in Jakarta is Infiltration Well. Several researches on this topic confirm the positive impact of building infiltration well on small catchment area. This study aims to understand the efficacy of infiltration well project on big basin area, the Ciliwung Basin. Ciliwung basin is divided into two sub-basin, Upstream Ciliwung and Downstream Ciliwung. The analysis is performed using volumetric abstraction of infiltration well volume and daily infiltration rate. 4 rainfall stations are used in this study, 2-gauge rainfall stations on each basin. Infiltration well capacity is tested with different return-period rainfall based on daily and storm-rainfall (3-days cumulative rainfall). The results show that by implementing 1 million infiltration wells at each sub-basin the abstraction volume is below 10% for 10-year return period rainfall and below 5% for 25-year return period rainfall.